The Impact of Periodontal Disease on Hospital Admission and Mortality During COVID-19 Pandemic - Larvin, Harriet; Wilmott, Sheryl; Wu, Jianhua; Kang, Jing (Frontiers in Medicine, 2020)
Introduction COVID-19 has had a huge impact on society and healthcare and it has been suggested that people with periodontal disease are at risk of having worse outcomes from the disease. The aim of this study was to quantify the impact of periodontal disease on hospital admission and mortality during the COVID-19 pandemic. Materials and Methods The study extracted UK Biobank participants who had taken a COVID-19 test between March and June 2020 (n = 13,253), of which 1,616 were COVID-19 positive (12%) and 11,637 were COVID-19 negative (88%). Self-reported oral health indicators of painful or bleeding gums and loose teeth were used as surrogates for periodontal disease, participants who did not report any of the aforementioned indicators were used as controls. Multivariable logistic regressions were used to obtain crude and adjusted odds ratios of COVID-19 infection, subsequent hospital admission, and mortality adjusted for demographics, BMI, biomarkers, lifestyle and co-morbidities. Results Painful gums, bleeding gums, and loose teeth were reported in 2.7%, 11.2% and 3.3% of participants with COVID-19 infection, respectively. Risk of COVID-19 infection in participants with painful or bleeding gums and loose teeth compared to controls was not increased (odds ratio [OR]: 1.10, 95% CI: 0.72– 1.69; OR: 1.15, 95% CI: 0.84-1.59). COVID-19 positive participants with painful or bleeding gums had a higher risk of mortality (OR: 1.71, 95% CI: 1.05-2.72) but not hospital admission (OR: 0.90, 95% CI: 0.59-1.37). Participants with loose teeth did not show higher risk of hospital admission or mortality compared to the control group (OR = 1.55, 95% CI: 0.87 – 2.77; OR: 1.85; 95% CI: 0.92-2.72). Conclusion There was insufficient evidence to link periodontal disease with an increased risk of COVID-19 infection. However, amongst the COVID-19 positive, there was significantly higher mortality for participants with periodontal disease. Utilisation of linked dental and hospital patient records would improve the understanding of the impact of periodontal disease on COVID-19 related outcomes.